Constraints on and dimensions of military interpreter neutrality - Snellman, Pekka (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
Military interpreters are soldiers assigned to interpretation duties. As soldiers, they may approach the notion of interpreter neutrality differently from civilian interpreters. This paper addresses the neutrality of military interpreters and contributes to the discussion on interpreter loyalty. The author’s own experiences and interviews with 14 Finnish military interpreters who have served in crisis management operations form the basis of this article. I examine neutrality as an ethical concept in its physical, professional, linguistic and cultural dimensions. Moreover, I explore the relationship between neutrality, loyalty, trust and identity. The results suggest that issues regarding neutrality are more complex for military interpreters than for their civilian counterparts. Furthermore, military interpreters may not always be considered neutral in the sense traditionally attributed to interpreters and with regard to the established ethical guidelines of the profession in particular.